Deviant Workplace Behavior as Emotional Action: Discriminant and Interactive Roles for Work-Related Emotional Intelligence. Issue 5 (20th October 2019) - Robinson, Michael D.; Persich, Michelle R.; Stawicki, Cassandra; Krishnakumar, Sukumarakurup
ABSTRACT: Employees are thought to engage in deviant workplace behaviors (e.g., sabotage, theft) when they are stressed, frustrated, or angry. Given the emotional nature of these actions, individual differences in work-related emotional intelligence (W-EI) should, potentially, be consequential. Three studies ( n s = 91, 198, & 147) examined this possibility by assessing variations in emotion perception and management skills with an ability measure specifically designed for the workplace context. Employees who received higher W-EI scores were less prone to both interpersonal deviance and organizational deviance and these relationships displayed discriminant validity as well as meaningful interactive effects with organizational stressors. The investigation extends our understanding of workplace deviance in a way that highlights an important role for work-related variations in emotional intelligence.